Modulation of benzylisoquinoline alkaloid biosynthesis by heterologous expression of CjWRKY1 in Eschscholzia californica cells - Yamada, Yasuyuki (PLoS One, 2017)
Transcription factors control many processes in plants and have high potentials to manipulate specialized metabolic pathways. Transcriptional regulation of the biosynthesis of monoterpenoid indole alkaloids (MIAs), nicotine alkaloids, and benzylisoquinoline alkaloids (BIAs) has been characterized using Catharanthus roseus, Nicotiana and Coptis plants. However, metabolic engineering in which specific transcription factors are used in alkaloid biosynthesis is limited. In this study, we characterized the effects of ectopic expression of CjWRKY1, which is a transcriptional activator with many targets in BIA biosynthesis in Coptis japonica (Ranunculaceae) and Eschscholzia californica (California poppy, Papaveraceae). Heterologous expression of CjWRKY1 in cultured California poppy cells induced increases in transcripts of several genes encoding BIA biosynthetic enzymes. Metabolite analyses indicated that the overexpression of the CjWRKY1 gene also induced increases in the accumulation of BIAs such as sanguinarine, chelerythrine, chelirubine, protopine, allocryptopine, and 10-hydroxychelerythrine in the culture medium. Previous characterization of EcbHLH1 and current results indicated that both transcription factors, WRKY1 and bHLH1, are substantially involved in the regulation of BIA biosynthesis. We discuss the function of CjWRKY1 in E. californica cells and its potential for metabolic engineering in BIA biosynthesis.